1999
DOI: 10.1007/s004150050510
|View full text |Cite
|
Sign up to set email alerts
|

Assessing multiple sclerosis activity: is the in vitro production of tumor necrosis factor-α, interleukins 2, 6, 4, and 10, and immunoglobulin G of value?

Abstract: Tumor necrosis factor (TNF) alpha, interleukins (IL) 2, 4, 6, and 10, and IgG oligoclonal bands (IgG OB) in vitro production was assessed, after whole-blood stimulation with lipopolysaccharide or concanavalin A, in 61 patients presenting with relapsing-remitting, relapsing-progressive, or chronic progressive multiple sclerosis. Multiple sclerosis patients were receiving no treatment or azathioprine (AZA), cyclosporin, cyclophosphamide, subcutaneous interferon (IFN) beta 1 a, or corticosteroids (CST). Statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
(51 reference statements)
3
2
0
Order By: Relevance
“…During the course, myelin antigen-induced IL-4 secretion was reduced after three months, which corroborates some previous findings of decreased IL-4 during IFN-β treatment (33,34), while other studies showed no difference (25,35), or increased IL-4 (28,36). The inconsistencies in previous data surely depend on differences in methodology as well as in time points of sampling.…”
Section: Th17-mediated Immunity Has Come Into Focus In Ms Because Of supporting
confidence: 85%
“…During the course, myelin antigen-induced IL-4 secretion was reduced after three months, which corroborates some previous findings of decreased IL-4 during IFN-β treatment (33,34), while other studies showed no difference (25,35), or increased IL-4 (28,36). The inconsistencies in previous data surely depend on differences in methodology as well as in time points of sampling.…”
Section: Th17-mediated Immunity Has Come Into Focus In Ms Because Of supporting
confidence: 85%
“…In our analyses, the group treated with IFN β demonstrated reduced levels of gene transcripts for IL4 compared to the vehicle group. The reduction of IL4 has already been observed in other studies, which demonstrated, in multiple sclerosis models, that treatment with IFN β acts by reducing the expression of such anti-inflammatory cytokine ( Schluep et al, 1999 ; Andersson et al, 2011 ; Kvarnström et al, 2013 ).…”
Section: Discussionsupporting
confidence: 65%
“…The lack of a correlation between the inflammatory mediators and disease severity in this study has already been observed [33, 34]. Our results in untreated patients may suggest that over time this group naturally presents a reduction of inflammatory mediators, but this could have been influenced by the small number in this group.…”
Section: Discussionsupporting
confidence: 47%